Is beta-carotene consumption associated with thyroid hormone levels? - Farasati Far, Bahareh; Broomand Lomer, Nima; Gharedaghi, Hossein; Sahrai, Hadi; Mahmoudvand, Golnaz; Karimi Rouzbahani, Arian (Frontiers in Endocrinology, 2023)
The pivotal role of thyroid hormones has been confirmed in growth, metabolism regulation, and reproduction, among others. Besides the influence of non-modifiable risk factors on the development of disorders related to thyroid hormones – hypothyroidism and hyperthyroidism as major ones – certain nutritional factors are also determining. Diets rich in selenium and iodine are conventionally acknowledged to be beneficial for the production and release of thyroid hormones. In addition to these known nutrients, relationships between serum levels of beta-carotene, a precursor to vitamin A (retinol), and diverse thyroid diseases have been proposed. Beta-carotene exerts anti-oxidant properties and its role in the prevention of various clinical conditions such as cancer, cardiovascular, and neurological diseases has been reported. In the case of thyroid diseases, studies have shown risen and reduced levels of beta-carotene in hypo- and hyper-thyroid patients, respectively. Reciprocally, the hormone produced by the thyroid gland namely thyroxine enhances the conversion of beta-carotene to retinol. Recently, the application of vitamin A derivatives as a potential therapeutic approach in thyroid malignancies has gained the interest of researchers in this topic more than ever. In this Review, we highlight the mechanisms through which beta-carotene/retinol and thyroid hormones interact and further review the findings of clinical studies in this regard.